A comparison expression analysis of CXCR4, CXCL9 and Caspase-9 in dermal vascular endothelial cells between keloids and normal skin on chemotaxis and apoptosis. Issue 2 (1st April 2022) - Dong, Xinhang; Zhang, Mingzi; Chen, Yuanjing; Li, Chengcheng; Wang, Youbin; Jin, Xiaolei
Abstract: This present study was designed to explore key biological characteristics and biomarkers associated with dermal vascular endothelial cells of keloids. GSE121618 dataset was downloaded in the Gene Expression Omnibus (GEO) Database, including the KECs group and NVECs group. Through GEO2R, we have screened the differentially expressed genes (DEGs) and performed gene ontology (GO), Gene Set Enrichment Analysis (GSEA), and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. Then, we constructed a protein–protein interaction (PPI) network and analyzed hub genes via the Search Tool for the Retrieval of Interacting Genes (STRING) Online Database and Cytoscape software. Furthermore, experiments were performed to validate the expression of selected genes, including H&E staining, immunohistochemical staining, Western blot, and RT-qPCR. A total of 1040 DEGs were selected with GEO2R online tools. Most of the enriched pathways and processes focus on cell migration, tube development, chemotaxis, cell motility, and regulation of apoptosis. With the assistance of STRING and Cytoscape, hub genes were selected. In our validation experiments of RT-qPCR, the mRNA expression of selected genes has significant differences between different groups in tissue and cell experiments. As was shown in immunohistochemical staining, the proteins of CXCR4, CXCL9, and Caspase-9 had higher expression levels in tissue samples of the Keloid group than the Normal skin group. Western blot and RT-qPCR in dermal vascular endothelial cell experiments were consistent with the aforementioned results. This study has provided a deeper analysis of the pathogenesis of dermal vascular endothelial cells in keloids. Genes of CXCR4, CXCL9, and Caspase-9 may influence the processes of inflammatory responses and vascular endothelial cell apoptosis to exert crucial effects in the development of keloids. Abbreviations : GEO: gene expression omnibus; DEGs: differentially expressed genes; KVECs: keloid vascular endothelial cells; NVECs: normal skin vascular endothelial cells; GO: gene ontology; KEGG: Kyoto encyclopedia of genes and genomes; PPI: protein protein interaction; BP: biological process; CC: cellular component; MF: molecular function; GSEA: gene set enrichment analysis; STRING: search tool for the retrieval of interacting genes; MCODE: molecular complex detection